THE CONTEMPORARY INFLUENCE OF THE GLOBALIZATION ON LINGUOCULTURE (Academia Science Repository, 2023)
This article looks at how linguistics and globalization are working together to have a real impact on every aspect of life. The conceptual analysis of the speech methodology is employed. A working hypothesis (core theoretical tenet) is put forth that there is a relationship between globalization and linguoculture that has the potential to have both positive and negative effects on customs, daily living, and life in general. The future of linguistic discourse research is described.